LEGAL POWER OF COVERNOTES MADE BY NOTARIES IN THE PROVISION OF CREDIT BY BANK - Tripetra Yokhanan Tarigan; Suprayitno; Rosnidar Sembiring; Agus Armaini RY; Doddy Safnul (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
The legal force of covernotes made by notaries in the granting of credit by banks is an important topic because of their vital role in banking and property transactions in Indonesia. Covernotes have become a common practice to speed up the credit disbursement process before all legal documents are processed, even though they are not authentic deeds. The status of covernotes raises serious questions about their legal force, because they are not explicitly regulated in the Notary Law. Cases of misuse of covernotes that have resulted in major losses for banks and customers increasingly emphasize the urgency of clarifying the legal status and limitations of the use of this instrument. The formulation of the problem in this study is, namely what is the function and legal position of covernotes made in the process of granting credit by banks, what is the authority of notaries in making covernotes in the disbursement of credit at banks, and what are the legal consequences of covernotes by notaries in the process of granting credit by banks. The research method used is empirical juridical, combining normative legal analysis with field research. Literature studies were conducted to examine legal regulations and literature, while field research included interviews with Notary Yetty Rosliana Sembiring and banking parties, as well as observations at notary offices. The data were analyzed qualitatively to understand the legal force of covernotes in bank credit practices. Covernotes in the bank credit process function as temporary collateral and instruments to accelerate credit disbursement, although they do not have the same legal force as notarial deeds. The authority of a notary to make a covernote is not explicitly regulated in the UUJN, but can be linked to the general authority of a notary in Articles 15 and 16 of the UUJN. The legal consequences of making a covernote that does not correspond to the facts can be very serious, including potential financial losses for the bank, criminal and administrative sanctions for notaries, civil lawsuits, and broader impacts on public trust in the notary profession and the banking system. This shows the importance of the integrity and caution of notaries in making covernotes, as well as the need for clearer regulations to regulate this practice in order to protect the interests of all parties involved and maintain the stability of the legal and banking systems.